Recent Study of Optical Activity and Faraday Rotation around the Edge Absorption of the Crystals \(Bi_12SiO_20\) and \(Bi_12SiO_20\):M (M = Co, Fe) - Todor Dimov; Ilia Iliev; Antonina Hristova (Advanced Aspects of Engineering Research Vol. 16, 2021)
In the spectral region of the excitons, reverse sign spectra of the Verdet constant V(\(ω\)) are observed in the optical active crystals Bi12 SiO20 and in the doped optical active crystals Bi12 SiO20:M (M=Co,Fe).. The spectral area, in which the sign of the doped crystals are changed, is moved in comparison to that of undoped crystals, and the energy of the photons \(ω\), at which an inversion of the siX of the V(\(ω\)) of doped crystals is observed, is less than the one of the undoped crystals. The reverse siX spectra ofthe doped crystals Bi12 SiO20 in the spectral region of the excitons is clarified By an exchange interaction between the localized paramagnetic ions Co^(2+) (or Fe) and the charge carriers forming the excitons. The main internal defect (Bi_Si^(3+) +h^+) in Bi12 SiO20 in Bi12 SiO20 describes this effect in undoped crystals. The changing of the six of V(\(ω\)) in this defect by one exchange interaction ofthe ligand ion O^- with a connected exciton (e^-+h^+) in this defect according to a simplified model.